Spinosad-induced stress on the maize weevil Sitophilus zeamais - Guedes, Raul Narciso C.; Vélez, Mayra; Walse, Spencer S. (Julius-Kühn-Archiv, 2018)
Although seldom considered, sublethal insecticide exposure may lead to harmful, neutral, or even beneficial responses that may affect (or not) the behavior and fitness of the exposed insects. Intriguingly, little is known about such effects on stored product insect pests and even less is available regarding the bioinsecticide, spinosad. Thus, we assessed the sublethal effects of spinosad on walking, feeding, drinking and mating behaviors of maize weevils (Sitophilus zeamais), also assessing their survival, reproductive output, and grain loss compared with maize weevils exposed to the pyrethroid deltamethrin (as positive control), and water only (negative control). Both spinosad and deltamethrin were able to effectively control the insects, although the latter caused a faster mortality than the former. Behavioral pattern changes were caused by both insecticides, especially deltamethrin, triggering irritability (i.e., avoidance after contact). Different feeding and drinking responses were also detected with significant avoidance to deltamethrin, but not to spinosad. Maize weevil couples sublethally exposed to deltamethrin and spinosad exhibited altered reproductive behavior, a likely consequence of their altered activity, but deltamethrin caused greater behavioral changes. Curiously, higher progeny emergence and grain loss were observed in deltamethrin-exposed insects, suggesting that this pyrethroid insecticide elicits hormesis in maize weevils that may compromise control efficacy by this compound. In contrast, such effect was not detected with spinosad, which did not elicit avoidance allowing the intended weevil exposure and control.